2021
DOI: 10.1080/21655979.2021.2005927
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane induces inflammation in primary hippocampal neurons by regulating Hoxa5/Gm5106/miR-27b-3p positive feedback loop

Abstract: Postoperative cognitive dysfunction (POCD) is a normal condition that develops after surgery with anesthesia, leading to deterioration of cognitive functions. However, the mechanism of POCD still remains unknown. To elucidate the POCD molecular mechanism, sevoflurane was employed in the present study to generate neuroinflammation mice model. Sevoflurane treatment caused inflammatory markers IL6, IL-10 and TNF-α high expression in primary hippocampal neurons and blood samples. Long non-coding RNA Gm5106 was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…HOXA5 has been previously proven to participate in the successive phases of central nervous system formation in embryonic and fetal stages [35]. Furthermore, HOXA5 suppression is potent to repress sevoflurane-induced inflammation in hippocampal neurons [15]. In our study, we disclosed that HOXA5 expression was elevated in propofol-induced neurons and declined in neurons with dexmedetomidine pretreatment.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…HOXA5 has been previously proven to participate in the successive phases of central nervous system formation in embryonic and fetal stages [35]. Furthermore, HOXA5 suppression is potent to repress sevoflurane-induced inflammation in hippocampal neurons [15]. In our study, we disclosed that HOXA5 expression was elevated in propofol-induced neurons and declined in neurons with dexmedetomidine pretreatment.…”
Section: Discussionsupporting
confidence: 51%
“…1d), and dexmedetomidine of 1 μM was chosen for follow-up experiments. HOXA5 was previously reported to be implicated with hippocampal neuronal inflammation [15]. HOXA5 expression levels in primary hippocampal neurons with different treatments were examined, and the results disclosed that HOXA5 expression was highly expressed in propofol-induced hippocampal neurons and under-expressed in dexmedetomidine-pretreated hippocampal neurons (P < 0.05, Fig.…”
Section: Dexmedetomidine Pretreatment Attenuates Propofolinduced Hipp...mentioning
confidence: 84%
See 1 more Smart Citation
“…However, in rodent models of encephalopathy, miR-21 and miR-34a negatively affected the permeability of the BBB, enhancing ischemia-induced leakage, by regulating tight junction proteins ( Ma et al, 2020 ). While the association between ncRNAs and POCD has been documented ( Twaroski et al, 2014 ; Li et al, 2018 ; Zhu and Ma, 2021 ), direct experimental evidence is lacking for the relationship between these ncRNA molecules and surgery/anesthesia-induced BBB disruption.…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…[ 31,32 ] However, it was reported that neurons also participate in neuroinflammation, which directly affecting the excitability of neurons, resulting in cognitive dysfunction and behavioral changes. [ 33,34 ] Importantly, we found that ZnO NPs‐induced neuroinflammation could originate from neurons. When we treated PC12 cells, we found that ZnO NPs entered the cells and induced apparent neuroinflammation in a dose‐ and time‐dependent manner (Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 92%